Association between retinal morphological characteristics and visual function in myopic traction maculopathy - Mengai Wu; Lifeng Chen; Yuanyuan Fan; Li Lin; Haidong Li; Zhijie Wang; Guanshun Yu; Xinyue Wu; Bin Zheng; Fan Lu (Photodiagnosis and Photodynamic Therapy)
Objective: To quantify retinal morphological characteristics in patients with myopic traction maculopathy (MTM), including myopic foveoschisis (MF), using optical coherence tomography angiography (OCTA) and investigate the correlation of MTM with visual function. Methods: This cross-sectional study included 19 eyes with myopic foveoschisis (MF) and foveal detachment (FD), 37 eyes with MF without FD, and 24 myopic eyes as control. OCTA was used to assess macular vessel density (VD) in the superficial capillary plexus (SCP), deep capillary plexus (DCP), foveal avascular zone (FAZ) area, FAZ perimeter, acircularity index, retinal thickness, and retinal volume. Microperimetry was performed to evaluate macular sensitivity (MS) covering the central 20°, 10°, 2° field centered at fovea. Correlations between macular microcirculation parameters, best-corrected visual acuity (BCVA), and MS were determined. Results: Compared to myopic controls, decreased macular parafoveal SCP VD, DCP VD, and the area VD in a 300 µm wide annulus surrounding the FAZ (FD-300), were found in the group of MF patients with FD, with (p = 0.007, 0.002, 0.005) respectively, and in the group of MF patients without FD, with (p = 0.01, 0.049, 0.009), respectively. In the MF without FD group, parafoveal SCP VD significantly correlated with BCVA, 2°MS, 10°MS, and 20°MS (p = 0.018, 0.002, 0.001, 0.029), FD-300 area density, retinal thickness, and retinal volume was significantly correlated with BCVA (p = 0.024, 0.015, 0.045). In the MF with FD group, DCP VD was significantly associated with 10° and 20° MS (p = 0.048, 0.014), as were retinal thickness and volume (all p < 0.05); however, FD-300 area density correlated significantly with BCVA (p = 0.014). Conclusions: Macular perfusion is closely associated with functional alterations in MTM. Macular VD could serve as a valuable biomarker for monitoring MTM progression and optimizing medical and surgical decisions.